The health and economic repercussions of declining MMR coverage in the United States - Chad R. Wells; Abhishek Pandey; Yang Ye; Carolyn Bawden; Rebecca Giglio; Charlene Wong; Velda Wang; Chelsea Cipriano; Lamia Ayaz; Gergely Röst; Seyed M. Moghadas; Meagan C. Fitzpatrick; et al. (Proceedings of the National Academy of Sciences, 2026)
The resurgence of measles in the United States, driven by declining childhood vaccination coverage, poses a substantial public health and economic threat. Using county-level Measles–Mumps–Rubella (MMR) vaccine coverage data and spatial incidence models, we quantified the economic burden of measles in 2025 and projected the impact of continued declines in vaccine uptake. In 2025, the estimated cost per measles case was $104,629 [50% high-density interval (HDI): $100,729 to $110,140], yielding a national burden of $244.2 million (50% HDI: $69.9 to $872.5 million). The cost per case varied widely across counties and was inversely correlated with local population immunity levels (Spearman correlation = −0.75, P < 0.001). We modeled a scenario in which coverage among children aged 0 to 6 y declined by 1% per year, reaching a 5% absolute reduction by year 5 relative to baseline. Under this scenario, we projected a nonlinear surge in cases, hospitalizations, and annual expenditures arising from outbreak response, direct medical costs, and productivity losses. This scenario produced 17,232 (50% HDI: 9,177 to 26,428), 4,085 (50% HDI: 2,184 to 6,210) hospitalizations, 36 (50% HDI: 19 to 54) deaths, and $1.50 (50% HDI: $0.90 to $2.85) billion in annual costs in 2030, with a cumulative cost of $7.77 billion (50% HDI: $5.56 to $11.58 billion) over 5 y. These findings demonstrate that even marginal reductions in MMR vaccine uptake can result in disproportionately large health and economic burdens.